2004
DOI: 10.1021/jp0486651
|View full text |Cite
|
Sign up to set email alerts
|

Can Cu+-Exchanged Zeolites Store Molecular Hydrogen? An Ab-Initio Periodic Study Compared with Low-Temperature FTIR

Abstract: Cu+-exchanged Si/Al 11:1 chabazite has been studied ab initio using the periodic CRYSTAL03 computer code with Hartree−Fock and the hybrid B3LYP Hamiltonians to characterize the structures and energetics of the Cu+ ion sitting preference and its interaction with H2. Two sites (I and IV) have been found to be stable for Cu+ ion:  site I, the most stable one, envisaging coordination in a six-membered zeolite ring and site IV in which the Cu+ ion sits in the largest eight-membered ring. Interaction of H2 gives ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
99
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 54 publications
12
99
0
Order By: Relevance
“…This is mainly due to the structure of the Cu + ions, which are highly coordinatively unsaturated and thus easily accessible to molecules moving inside the zeolite channels [34,39,42]. Very recently, it has been reported that intrazeolitic Cu + species can also bind molecular H 2 at room temperature [30,93,94], a rather surprising finding when considering that the only Cu + (H 2 ) complex previously known was the [Cu(h 2 -H 2 )Cl] adduct isolated by cocondensation of CuCl and H 2 in an Ar matrix [95]. The interest of a microporous system able to reversibly adsorb H 2 at room temperature is self-evident, because it satisfies one of the pre-requisites for hydrogen storage [71].…”
Section: H 2 Adsorption On Exchanged Cu + -Zsm-5: Ft-ir Experiments Amentioning
confidence: 99%
See 2 more Smart Citations
“…This is mainly due to the structure of the Cu + ions, which are highly coordinatively unsaturated and thus easily accessible to molecules moving inside the zeolite channels [34,39,42]. Very recently, it has been reported that intrazeolitic Cu + species can also bind molecular H 2 at room temperature [30,93,94], a rather surprising finding when considering that the only Cu + (H 2 ) complex previously known was the [Cu(h 2 -H 2 )Cl] adduct isolated by cocondensation of CuCl and H 2 in an Ar matrix [95]. The interest of a microporous system able to reversibly adsorb H 2 at room temperature is self-evident, because it satisfies one of the pre-requisites for hydrogen storage [71].…”
Section: H 2 Adsorption On Exchanged Cu + -Zsm-5: Ft-ir Experiments Amentioning
confidence: 99%
“…It is widespread opinion that a large shift (of the order of À1000 cm À1 ) of theñ(HH) frequency in Cu + (H 2 ) molecular complexes in side-on configuration is the symptom of a strong interaction involving weak electrostatic (charge-induced dipole and charge quadrupole) and strong chemical (donation from the H 2 s orbital and back-donation from the 3dp Cu + orbitals) contributions [30,93,95,97]. The s donation in the 4s orbital and back-donation from the dp orbitals of Cu + are synergistic and lead to the formation of three center Cu + (H 2 ) covalent bonds, where back-donation weakens the H-H bond to a very large extent.…”
Section: Evolution Of the Cu + (H 2 ) Adducts At 15 K As A Function Omentioning
confidence: 99%
See 1 more Smart Citation
“…Following our work on the CoALPOs, we now report a preliminary INS study of molecular hydrogen interacting with a copper ZSM5. It has been claimed that the interaction of H 2 with Cu ZSM5 [13][14][15][16][17][18] and Fe ZSM5 [19] is strong.…”
Section: Introductionmentioning
confidence: 99%
“…In protonated zeolites, binding of H 2 molecules increased with the Brønsted acidity of the zeolite [8]. From theoretical studies the H 2 interaction with alkali metal cations is dominated by the polarisation contribution [14]. That polarisation of the H 2 molecule [9] is significant in the binding we now show experimentally by inelastic neutron scattering (INS) [15].…”
Section: Introductionmentioning
confidence: 61%